MUZAKKI PERCEPTION OF ISLAMIC STATE EXPENDITURE: AN INTERPRETIVE ANALYSIS OF JUSTICE AND POVERTY ALLEVIATION EFFECTIVENESS IN BONE REGENCY - Nur Fadilla Azis; Herianti (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2025)
This research analyzes the perception of Muzakki (Zakat payers) regarding Islamic local expenditure in Bone Regency, focusing on distributive justice and its effectiveness in poverty alleviation. Zakat, Infaq, and Sadaqah (ZIS) instruments are crucial for regional socio-economic development, but Muzakki’s perception of the management of these funds significantly affects the social legitimacy and sustainability of Islamic fiscal programs. The analysis employs a qualitative documentary approach, reviewing regulations on Islamic local expenditure, BAZNAS (National Zakat Agency) Bone Regency reports, and Islamic economic literature.The results indicate that although BAZNAS Bone has enhanced transparency and accountability through report publications and a digital system, the aid distribution is not yet fully equitable, especially in remote rural areas. The effectiveness of Islamic local expenditure is considered limited because aid and empowerment programs are temporary, lacking sustainable impact. Furthermore, the integration of ZIS with local expenditure is not yet optimal. Based on these findings, improvement strategies are recommended, including: increasing transparency, integrating ZIS with government programs, developing sustainable empowerment programs for Mustahik (Zakat recipients), and providing adequate information to build Muzakki trust. This study confirms that Muzakki perception is a critical indicator for measuring the social legitimacy and effectiveness of Islamic fiscal policy at the local level.